Analysis of thermally driven structural changes, genome release, disassembly, and aggregation of recombinant AAV by CDMS - Lauren F. Barnes; Benjamin E. Draper; Martin F. Jarrold (Molecular Therapy: Methods & Clinical Development, 2022)
Charge detection mass spectrometry (CDMS) was used to analyze recombinant adeno-associated virus serotype 8 (rAAV8) vectors after incubation at elevated temperatures. rAAV8 vectors with a range of genomes of interest (GOIs) from 2.22 to 4.84 kb were investigated. For the shorter GOIs, GOI release occurred at surprisingly low temperatures (15 min at 45°C for cytomegalovirus [CMV]-GFP). The released DNA and intermediates with the GOI extruded from the capsid were detected. The temperature required to release the short GOIs is well below the 65°C incubation temperature required to disassemble the empty rAAV8 capsid. The temperature for GOI release increased with its GOI length. With the longer GOIs, the GOI stabilized the capsid so that it remained intact under conditions that would disassemble the empty particle. After incubation at 65°C, the main species in the CDMS mass distributions for the longer GOIs was the vector with the GOI. However, for GOIs longer than the wild-type genome (∼4.7 kb), the stability diminished, and genome release occurred at a lower temperature. Heterogeneous DNA fragments from the host cells or plasmids is released at a lower temperature than the longer GOIs, suggesting that the GOIs have a feature that resists early release.